Glia and TRPM2 Channels in Plasticity of Central Nervous System and Alzheimer’s Diseases - Jing Wang; Michael F. Jackson; Yu-Feng Xie (Neural Plasticity)
Synaptic plasticity refers to the ability of neurons to strengthen or weaken synaptic efficacy in response to activity and is the basis for learning and memory. Glial cells communicate with neurons and in this way contribute in part to plasticity in the CNS and to the pathology of Alzheimer’s disease (AD), a neurodegenerative disease in which impaired synaptic plasticity is causally implicated. The transient receptor potential melastatin member 2 (TRPM2) channel is a nonselective Ca2+-permeable channel expressed in both glial cells (microglia and astrocytes) and neurons. Recent studies indicated that TRPM2 regulates synaptic plasticity as well as the activation of glial cells. TRPM2 also modulates oxidative stress and inflammation through interaction with glial cells. As both oxidative stress and inflammation have been implicated in AD pathology, this suggests a possible contribution of TRPM2 to disease processes. Through modulating the homeostasis of glutathione, TRPM2 is involved in the process of aging which is a risk factor of AD. These results potentially point TRPM2 channel to be involved in AD through glial cells. This review summarizes recent advances in studying the contribution of TRPM2 in health and in AD pathology, with a focus on contributions via glia cells.